Clinical characteristics of cephalalgia at patients with arterial hypertension during intermittent fasting. - Liu Chun; O. V. Pohorielov (Medičnì Perspektivi)
The study of the effectiveness and safety of intermittent fasting (IF) at 185 patients aged from 25 to 75 years (mean age – 48,6 years) with arterial hypertension (AH) and headache was carried out. AH was seen as the most likely factor of cerebral discirculation and associated cephalgia. Patients volunteered to maintain a short-term dietary restriction with terms of 16 or 24 hours once in 7 days over a period of 4 weeks. During this period, 43 patients stopped participation in the study, of which 31 - at 24-hour IF and 12 - at 16-hour IF. The assessment of the influence on cephalgia was considered positive when the score of visual analog scale (VAS) was decreased by 2 or more points and / or there was a significant decrease in the duration and frequency of cephalgia attacks. In a rhythmic diet with a 16-hour food intake missing, a positive result was registered at 35% (37,25% of young patients, 40,48% – of  average and 28,57% of the elderly) without a significant difference between ages. The effectiveness of a 24-hour type of IF was higher and made up about 75% in all age groups. Negative side effects of IF that would require its termination due to objective reasons (threatening changes in blood pressure, syncope states and others) were not recorded, the most common complaints were the feeling of hunger (from 50 to 76% with a difference in age), psychological tension, uncertain anxiety (on average about 32%). The authors consider that such a psychological feature - namely, the impossibility and unwillingness to endure short-term fasting was a main factor of refusal to continue the treatment regimen, and within certain limits prevents the wider use of IF method in the treatment of cephalgia. In general, the efficacy of a 24-hour IF compared with a 16-hour type was significantly higher, without severe side effects.